Spurensuche einer Rezeptionsgeschichte Alexander von Humboldt und Johann Gottfried Herder - Bernhard Hunger (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien, 2009)
Article in German, Abstracts in English, German and Spanish.Alexander von Humboldt's work displays traces of Johann Gottfried Herder which are as multifaceted as the references to the latter are scarce. In light of this aspect, the present essay focuses on Humboldt's Physiognomy of Plants (1806), in which he explicitly mentions Herder for the first time in a publication. Two years later, the text is incorporated within Aspects of Nature (1808 ff.). In the third edition of Aspects (1849), Herder's name is curiously omitted. This omission is incomprehensible both in form and content. The historical context characterising the years between 1805 and 1808 suggests that Humboldt's references to Herder must have been made very deliberately. Humboldt's correspondence with the historian Johannes von M¸ller and other sources shows that Humboldt carefully studied Herder's writings. As the publisher of Herder's complete works, Johannes von M¸ller, who was Humboldtís friend and neighbour at the time, even considered Humboldt to be a direct descendant of the Herder school.